State of knowledge of the Tenebrionidae (Insecta: Coleoptera) in Colombia based on bibliographic revision - Oscar Ascuntar-Osnas; Pablo A. López-Bedoya; Aaron D. Smith; M. Andrew Johnston; Jennifer C. Girón (Caldasia)
Tenebrionidae is one of the most diverse families in Coleoptera. However, research on the family in Colombia is limited. Based on a comprehensive literature review, a list of tenebrionid species known from the country was compiled and the state of knowledge is analyzed. Based on this information, the Ten-ebrionidae in Colombia are represented by 326 species, organized into 95 genera (seven subgenera), 30 tribes, and nine subfamilies. Cundinamarca, including Bogotá, presents the highest number of recorded species with 52, followed by Valle del Cauca with sixteen, and Bolívar with thirteen; eight departments have records for only a single species, and ten do not have records of any tenebrionid species. Potential reasons for the historically limited research on Colombian tenebrionids are discussed and actions to reduce these knowledge gaps are proposed.